An evaluative framework for examining the use of land value capture to fund public transportation projects. (July 2019) - Mathur, Shishir
Highlights: Major success factors and challenges to the use of land value capture to fund public transportation projects are identified. Land Value Capture tools used to fund the metro rail system in Delhi, India—Delhi Metro—are reviewed. A framework is presented to evaluate whether, how, and how well land value capture (LVC) tools are funding Delhi Metro. Several intertwined factors, many related to land use planning and policy, limit magnitude of land value capture revenues. Abstract: The proposed study contributes to the land use policy literature by first reviewing the existing literature to identify a set of major success factors and challenges to the use of land value capture (LVC) to fund public transportation projects. Next, it reviews LVC tools used to fund the metro rail system in Delhi, India—Delhi Metro. Finally, it uses the success factors and challenges identified in the study to present a framework for evaluating whether, how, and how well LVC tools are being used to fund Delhi Metro. This paper finds that several intertwined factors, many related to land use planning and policy, limit the magnitude of LVC revenues. These factors include a lack of consistency between the plans of transit agencies and local governments, that has led to poor planning for transit-oriented development (TOD) inside and around station land; the inability of transit agencies to control land use and zoning for and around the station; and over-reliance on capturing value from new properties instead of from all properties that benefit from the metro system.